2008 IEEE International Conference on Robotics and Automation 2008
DOI: 10.1109/robot.2008.4543251
|View full text |Cite
|
Sign up to set email alerts
|

Gaussian mixture models for probabilistic localization

Abstract: Abstract-One of the key tasks during the realization of probabilistic approaches to localization is the design of a proper sensor model, that calculates the likelihood of a measurement given the current pose of the vehicle and the map of the environment. In the past, range sensors have become popular for mobile robot localization since they directly measure distance. However, in situations in which the robot operates close to edges of obstacles or in highly cluttered environments, small changes in the pose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 14 publications
(25 reference statements)
0
14
0
Order By: Relevance
“…This set of experiments is designed to investigate the case that the robot is not able to localize itself at different locations with the same robustness. In our previous work [15], we demonstrated that whenever the robot traverses regions close to obstacles, doorways, or clutter, the likelihood of the true position decreases. In the case of global localization using a particle filter this leads to serious problems because the particles at these positions have a high risk of being depleted.…”
Section: A Likelihood Evaluationmentioning
confidence: 79%
See 4 more Smart Citations
“…This set of experiments is designed to investigate the case that the robot is not able to localize itself at different locations with the same robustness. In our previous work [15], we demonstrated that whenever the robot traverses regions close to obstacles, doorways, or clutter, the likelihood of the true position decreases. In the case of global localization using a particle filter this leads to serious problems because the particles at these positions have a high risk of being depleted.…”
Section: A Likelihood Evaluationmentioning
confidence: 79%
“…Due to that, in this paragraph we will describe typical likelihood models for range sensors and we shortly will introduce the likelihood models of our previous work [14], [15]. Afterwards, we will present our new high dimensional Gaussian mixture model that is able to represent multi-modalities in the likelihood function as well as dependencies between the individual laser beams.…”
Section: B Likelihood Models For Range Sensorsmentioning
confidence: 99%
See 3 more Smart Citations